From Determinants to Behavioral Outcomes: The Role of Rural Tourism Destination Image in Shaping Recommendation and Revisit Intentions - Xingshi, Zhang; Ahmad, Wasim (International Review of Management and Marketing, 2026)
This study investigates the determinants and outcomes of rural tourism destination image, focusing on rural homestays in China. Based on Destination Image Theory and Place Attachment Theory, it examines how destination location, natural and cultural attractions, infrastructure, gastronomy, accommodation, rural lifestyle, and local community shape tourists' perceptions and intentions, especially intention to revisit and intention to recommend. A total of 378 valid questionnaires were collected and analyzed using PLS-SEM. The results show that destination location, cultural attractions, infrastructure, gastronomy attractions, accommodation attractions, rural lifestyle, and the local community significantly improve rural tourism destination image. Natural attractions do not show a significant effect. Rural tourism destination image has a positive effect on perceived destination quality, perceived value, and destination attachment. Destination attachment also increases tourists’ intention to revisit and intention to recommend. Memorable tourism experience strengthens the relationship between DAM and revisit intention, but it does not significantly influence the relationship between DAM and recommendation intention. This comprehensive exploration aims to provide actionable strategies for rural tourism stakeholders in China to foster sustainable tourism growth and meaningful visitor experiences.